Respuesta :

Padoru

Hello there! We are given the following equation and want to solve for f(f(x))

[tex]f(x)=x^2+1[/tex]

f(f(x)) will be replacing the "x" in f(x) with the entire equation of f(x), it sounds a bit complicated, but this is what it will look like:

[tex]f(f(x))=(x^2+1)^2+1[/tex]

Using FOIL or the formula for squaring a binomial gives us:

[tex]=(x^4+2x^2+1)+1[/tex]

Open parenthesis and simplify

[tex]= x^4+2x^2+2[/tex]

This should be your answer. Let me know if you need any clarifications, thanks!

~ Padoru

Answer:

Step-by-step explanation:

hello :

if f(x) = x² + 1

f(f(x)) = f( x² + 1)  = (x² + 1)² +1